DOI: 10.18122/td/1719/boisestate
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Regeneration, Rooting, and Cloning of Artemisia tridentata

Abstract: Artemisia tridentata (big sagebrush) is an ecologically important shrub found in western North America. In vitro techniques can be applied to big sagebrush for the purpose of studying gene function, genotypic and phenotypic plasticity studies, cloning, genotypic preservation, and restoration. I performed experiments to develop an indirect organogenesis protocol to regenerate whole Wyoming big sagebrush plants from leaf explants. Callus formation frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…Finally, our preliminary experiment has shown that diploid A. tridentata subsp. tridentata shoot tip cuttings can form adventitious roots in a medium lacking growth regulators [23]. However, the results suggested marked differences in adventitious root formation depending on the seedling from where the shoot tips originated; some individual seedlings produced shoot tips that either rooted at a very low frequency or not at all.…”
Section: Introductionmentioning
confidence: 93%
“…Finally, our preliminary experiment has shown that diploid A. tridentata subsp. tridentata shoot tip cuttings can form adventitious roots in a medium lacking growth regulators [23]. However, the results suggested marked differences in adventitious root formation depending on the seedling from where the shoot tips originated; some individual seedlings produced shoot tips that either rooted at a very low frequency or not at all.…”
Section: Introductionmentioning
confidence: 93%
“…medicinal, ceremonial tissue culture *ˆMexico [118] Gentiana kurroo medicinal shoot culture * India [146] Eucalyptus spp. medicinal tissue culture * Australia, Tasmania [147] Rhinacanthus nasutus medicinal, dye tissue culture * Southwest Bengal [148] Gethyllis multifolia medicinal hydro culture * Worcester, South Africa [149] Agathosma betulina medicinal, food micropropagation * Western Cape, South Africa [150] Wrightia tinctoria medicinal stem cuttings * India [151] Aristolochia ringens medicinal root, stem cuttings * Nigeria [152] Manihot esculenta medicinal, food micropropagation * Global distribution [153] Artemisia tridentata medicinal, ceremonial micropropagation * Western North America [154] Swertia mussotii medicinal, ceremonial micropropagation * Qinghai-Tibet Plateau, China…”
Section: Scientific Name Traditional Uses In Vitro Methods Used Geogr...mentioning
confidence: 99%